Monocyte and Macrophage-Mediated Pathology and Protective Immunity During Schistosomiasis - Souza, Camila Oliveira Silva; Gardinassi, Luiz Gustavo; Rodrigues, Vanderlei; Faccioli, Lúcia Helena (Frontiers in Microbiology, 2020)
Infection by Schistosoma parasites culminates in a chronic granulomatous disease characterized by intense tissue fibrosis. Along the course of schistosomiasis, diverse leukocytes are recruited for inflammatory foci. Innate immune cell accumulation in Th2-driven granulomas around Schistosoma eggs is associated with increased collagen deposition, while monocytes and macrophages exert critical roles during this process. Monocytes are recruited to damaged tissues from blood, produce TGF- and differentiate into monocyte-derived macrophages (MDMs), which become alternatively activated by IL-4/IL-13 signaling via IL-4Rα (AAMs). AAMs are key players of tissue repair and wound healing in response to Schistosoma infection. Alternative activation of macrophages is characterized by the activation of STAT6 that coordinates the transcription of Arg1, Chi3l3, Relma and Mrc1. In addition to these markers, monocyte-derived AAMs also express Raldh2 and Pdl2. AAMs produce high levels of IL-10 and TGF-β that minimizes tissue damage caused by Schistosoma egg accumulation in tissues. In this review, we provide support to previous findings about the host response to Schistosoma infection reusing public transcriptome data. Importantly, we discuss the role of monocytes and macrophages with emphasis on the mechanisms of alternative macrophage activation during schistosomiasis.